2002
DOI: 10.1093/aje/kwf043
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Psychosis: A Longitudinal Population-based Study

Abstract: Cannabis use may increase the risk of psychotic disorders and result in a poor prognosis for those with an established vulnerability to psychosis. A 3-year follow-up (1997-1999) is reported of a general population of 4,045 psychosis-free persons and of 59 subjects in the Netherlands with a baseline diagnosis of psychotic disorder. Substance use was assessed at baseline, 1-year follow-up, and 3-year follow-up. Baseline cannabis use predicted the presence at follow-up of any level of psychotic symptoms (adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
512
3
36

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 810 publications
(592 citation statements)
references
References 37 publications
36
512
3
36
Order By: Relevance
“…The basis of why some subjects but not others experienced transient but significant psychotic symptoms is not clear, but is of considerable interest. Several large sample studies (n ¼ 7000-50 0000) suggest that moderate (more than 20 times) lifetime exposure to cannabis is associated with a higher risk to develop schizophrenia later on (Andreasson et al, 1988;van Os et al, 2002;Zammit et al, 2002). Therefore, we examined the relationship between lifetime cannabis exposure (Table 2) and psychotomimetic effects of D-9-THC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of why some subjects but not others experienced transient but significant psychotic symptoms is not clear, but is of considerable interest. Several large sample studies (n ¼ 7000-50 0000) suggest that moderate (more than 20 times) lifetime exposure to cannabis is associated with a higher risk to develop schizophrenia later on (Andreasson et al, 1988;van Os et al, 2002;Zammit et al, 2002). Therefore, we examined the relationship between lifetime cannabis exposure (Table 2) and psychotomimetic effects of D-9-THC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has confirmed such links. Early-onset cannabis use increases the risk of developing schizophrenia (Arseneault et al, 2002;Fergusson et al, 2003;van Os et al, 2002) as well as a worsen course of the disorder (Green et al, 2004;Veen et al, 2004). Several epidemiological studies report that early regular use of cannabis increases the risk of initiation of the use of other illicit drugs (Agrawal et al, 2004;Fergusson and Horwood, 2000;Lynskey et al, 2003;Yamaguchi and Kandel, 1984), supporting the cannabis gateway hypothesis of cannabis as a steppingstone toward abuse of other drugs.…”
Section: Introductionmentioning
confidence: 93%
“…Previous work has shown that subclinical psychotic experiences measured with valid self-report questionnaires show longitudinal continuity with more severe states of psychosis, such as psychotic illness (Chapman et al, 1994;Hanssen et al, 2005) and are transmitted in families . Similarly, established risk factors for psychotic illness also affect the occurrence of these subclinical psychotic experiences (Krabbendam et al, 2005;Nuechterlein et al, 2002;van Os et al, 2002van Os et al, , 2000van Os et al, , 2001. Subclinical psychotic experiences as measured with the CAPE can therefore be considered as a proxy for an underlying liability to psychosis (Johns and van Os, 2001).…”
Section: Psychosis Measuresmentioning
confidence: 99%